Rūznāmah-'i safar-i Māzardarān - Nāṣir al-Dīn Shāh, Shah of Iran, 1831-1896 (Intishārāt-i farhang-i Īrān zamīn ; 24) (Silsilah-'i chāp-i Iawhī va 'aksī ;, 1977)
Travel impressions of Mazandaran, Iran, 1875 or 1976.